Impact of Performance Appraisal Strategy on Employee Productivity: Evidence from Selected Nigerian Banks (Journal of Management and Social Sciences, 2020)
Many organisations experience low productivity despite their acclaimed effective performance appraisal system. In Nigeria, many organisations, especially banks are experiencing low productivity and performance due to ineffective appraisal system. This study, therefore, seeks to investigate the impact of performance appraisal strategy on employee performance with specific reference to selected Nigerian banks. Five banks were selected through purposive method. Judgmental sampling technique was also used to select Head of Operation, Accountant, Auditor, and Branch Manager from 5 branches of the selected banks in Ibadan metropolis, Oyo State, Nigeria. One hundred respondents served as sample size for the study. The data collection instrument for the study was structured questionnaire to elicit information. Simple percentage and Ordinary Least Square (OLS) were adopted for data analysis. Findings show that the overall assessment of performance appraisal in Nigerian banks has a significant impact on employee performance and also reveals that most Nigerian banks make use of the ranking method to assess their staff. Consequently, the study recommends that bank authorities should not appraise the performance of employees based on the deposit target, but on their accomplished duties and responsibilities.